Complex dynamics of a heavy symmetrical gyroscope under a parametric nonlinear damping - Pomalegni, G.F.; Nourou, Y.; Miwadinou, Clément; Monwanou, Vincent A. (Zielona Góra: Uniwersytet Zielonogórski)
This paper analyzes the chaos and coexistence of attractors of a heavy gyroscope with parametric nonlinear damping. After having found the mathematical model of the dynamics, we used the multiple scale technique to look for secondary resonances. Subsequently, the amplitude of the harmonic oscillations is determined based on the harmonic balance technique. Impact of each of the system parameters is analyzed on the amplitudes and frequency of resonances.
Keywords: parametric nonlinear damping; sub-harmonic resonances; gyroscope; coexistence of attractors; chaos